Desempenho produtivo, características de carcaça e qualidade de carne de cabritos "mamão" em diferentes sistemas de criação - Santos, Norivaldo Lima (2014)
This study aimed to evaluate effect of three different rearing systems: traditional system- TS; intensive feedlot system without concentrated – IFSWC and intensive feedlot system to concentrate- IFSTC on animal performance, carcass characteristics and meat quality of dairy goats kids. The experiment was conducted simultaneously in two properties located in the semiarid region of the state of Paraíba, Brazil, with different management systems offspring. Thirty newborns goat kids, no castrated with initial weight of 3.35 kg ± 0.65 kg crossbreed Parda Alpina x undefined breed (SPRD), distributed in a completely randomized design with three treatments and ten were used repetitions. During the experimental period, the animals were subjected to semi - intensive management with their mothers in breastfeeding and supplementation with concentrated feed and forage cactus. In both intensive systems , the kids were separated from their mothers, artificially fed cow's milk to the limit of 1.5 l/day and supplemented with hay Tifton. In both systems, the animals were slaughtered when they reached 12 kg liveweight. It was observed that the goats had lower IFSWC undergoing confinement period (67.2 days ), with a lower unit cost of production (R$ 172.81) and better carcass traits (fat thickness and finish) the than the others. Moreover,the meat obtained from animals raised in IFSWC showed paler color, more pronounced and with high dietary indicators of meat quality ( higher content of linoleic acid and higher PUFA:SFA and lower w6 : w3 ) aroma, which qualifies for high-quality beef markets.